2007
DOI: 10.1051/0004-6361:20077450
|View full text |Cite
|
Sign up to set email alerts
|

On comparison and combination of catalogues of radio source positions

Abstract: Context. Radio source catalogues (RSCs) obtained from very long baseline interferometry (VLBI) observations are recommended by the International Astronomical Union (IAU) as realizations of the International Celestial Reference Frame (ICRF). As the accuracy of the VLBI observations is improving with time, development of more accurate methods of RSC construction is a topical problem. Aims. In this paper we search for an optimal method of representation of the RSC systematic errors and investigate a possibility f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 7 publications
0
18
0
Order By: Relevance
“…They were submitted by JPL (Caltech/NASA Jet Propulsion Laboratory, USA), and USNO (US Naval Observatory, USA). A brief description of the input catalogs is given in Table 1 ( Sokolova & Malkin 2007). This section is divided into two subsections.…”
Section: Using Two Different Quasar Catalogs To Improve the Icrf-ext2mentioning
confidence: 99%
See 1 more Smart Citation
“…They were submitted by JPL (Caltech/NASA Jet Propulsion Laboratory, USA), and USNO (US Naval Observatory, USA). A brief description of the input catalogs is given in Table 1 ( Sokolova & Malkin 2007). This section is divided into two subsections.…”
Section: Using Two Different Quasar Catalogs To Improve the Icrf-ext2mentioning
confidence: 99%
“…Different methods were used to obtain a combined RSC with (Arias et al 1988) being the first of them, and others were proposed by Walter (1989aWalter ( , 1989b and Yatskiv (1990). In accordance with Sokolova (2007), appropriate use of individual catalogs with common sources provides an improvement of each individual catalog. Among the general aims regarding this subject, we can point out the comparative study between catalogs and ICRF defining sources by considering a rigid frame (only rotations), avoiding deformations, and considering the densification of the ICRF in a twofold sense: the increased amount of defining sources and the densification in its wider sense of the catalog.…”
Section: Introductionmentioning
confidence: 99%
“…Studies comparing radio source catalogues have found that ad-hoc methods which systematically shift source declinations by different amounts depending on declination are effective in improving the agreement between different catalogues (Arias & Bouquillon 2004;Sokolova & Malkin 2007), and it is possible this is partly an effect of a declination degeneracy.…”
Section: Comparing Cataloguesmentioning
confidence: 99%
“…Other interesting transformations based on Legendre-Fourier functions have been developed by Sokolova & Malkin (2007) to model differences between catalogues of several hundreds of sources. Here, we only keep degree 1 and 2 describing translations and rotations, respectively.…”
Section: Generation Of Source Coordinate Time Seriesmentioning
confidence: 99%